Nursing Students’ Attitudes to the Recording and Protection of Patients’ Health Data: A Cross-Sectional Study - Yılmaz, Dilek; Uysal, Oktay (Makara Journal of Health Research, 2024)
Background: Understanding nursing students’ attitudes toward patient data protection is crucial, as it can affect their future practice and adherence to legal and ethical standards. The primary aim of this study was to assess nursing students’ attitudes toward the recording and protection of patients’ health data. Methods: In this descriptive and cross-sectional study, 460 students were selected using the convenience sampling method. The intention was to contact the whole research population; however, data were collected from those who agreed to participate in the study and who completed the data collection form, which accounted for 70% of the population. For data collection, a five-question student description form and the personal health data recording and protection attitude form for nursing students, consisting of 31 questions checked for language validity, were used. The independent samples t-test and one-way variance analysis were used in independent groups. Results: The students’ mean score on the personal health data recording and protection attitude form for nursing students total was 3.96 ± 0.56. The attitudes to the recording and protection of patients’ health data of female students, in their second-year of study, who had knowledge concerning personal data and health data, who desired to work in fields of practice related to their studies, and whose levels of communication with patients in their fields of practice were significantly better than those of other students (p = 0.001, p = 0.001, p = 0.000, p = 0.000, p = 0.001, respectively). Conclusions: Nursing students demonstrated positive attitudes to the recording and protection of patients’ data, and certain independent variables affect this. The results of the study may provide nursing educators with an opportunity to carry out interventions relating to factors that affect the attitudes of nursing students to the recording and protection of patients’ health data. Qualitative and interventional studies on the research topic with larger samples are warranted.